Wild cherry (Prunus microcarpa) ameliorates azoxymethane-induced aberrant crypt foci in vivo: Depicted molecular mechanisms - Ahmed A. Abduljabbar; Parween A. Ismail (ARO-The Scientific Journal of Koya University, 2025)
Colorectal cancer is the third diagnosed cancer across the globe despite modern therapeutic interventions. Prunus microcarpa has been consumed as a therapeutic tea for several human disorders; therefore, the study investigates the chemoprotective effects of Prunus microcarpa against azoxymethane-induced aberrant crypt foci (ACF) in rats. Fifty Sprague-Dawley rats were divided into five groups: a normal control group and untreated rats given saline; a reference group treated with 5-fluorouracil; and two groups treated with 500 mg/kg methanolic extracts of fruits and stems (MEPMF and MEPMS), separately, for two months. Additionally, all rats, except the normal controls, were injected with azoxymethane twice a week for two consecutive weeks and consumed sodium dextran sulfate-mixed water for seven days.